2022
DOI: 10.1590/1980-549720220013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend of simultaneous risk factors for chronic non-communicable diseases: National School Health Survey 2009, 2012, 2015

Abstract: Objective: To analyze the temporal trend of simultaneous occurrence of behavioral risk factors for chronic non-communicable diseases in Brazilian school adolescents. Methods: Ecological time-series study that analyzed data from the three editions of the National Survey of School Health with students in the 9th year of public and private schools. Cluster analysis was performed to identify the simultaneity of the following factors: irregular consumption of fresh or minimally processed foods, regular consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A temporal trend analysis on the behavioral risk factors for chronic NCDs in Brazilian school adolescents between 2009, 2012 and 2015 10 indicated that the regular consumption of processed and ultra-processed foods was the second risk factor for diseases, second only to little physical activity; the authors also found a tendency towards a decrease in the participation of UP foods in the diet, together with an increase in irregularity in the consumption of fresh and minimally-processed foods.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A temporal trend analysis on the behavioral risk factors for chronic NCDs in Brazilian school adolescents between 2009, 2012 and 2015 10 indicated that the regular consumption of processed and ultra-processed foods was the second risk factor for diseases, second only to little physical activity; the authors also found a tendency towards a decrease in the participation of UP foods in the diet, together with an increase in irregularity in the consumption of fresh and minimally-processed foods.…”
Section: Resultsmentioning
confidence: 99%
“… The findings support the role of ultra-processed foods in the obesity epidemic in Brazil. Araújo et al 10 (2022) Ecological 173,310 school adolescents, from PeNSE 2009, 2012 and 2015. To analyze the temporal trend of the simultaneous occurrence of behavioral risk factors (RF) for NCDs in Brazilian school adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations